Effective Leadership in Times of Organizational Crises: The Interplay of Risk Perceptions, Trust, and Diversity - Osunde, Carl; Mayowa, Agboola Gbenga (Prabandhan: Indian Journal of Management, 2013)
Organizations are faced with challenges which arise from the interplay of risk perceptions, trust, and diversity. Diversity is a broad term which highlights numerous differences and similarities in an organization in the areas of culture, age, qualification, gender, and attitudes in the workplace. Risk perceptions may have a more dominant impact on trust and leadership effectiveness than previously assumed. Trust has been identified as being essential in the effectiveness of charismatic leaders (Bass, 1985) and as being critical when leaders communicate information regarding a risky situation or crisis (Kasperson, Kasperson, Pidgeon, & Slovic, 2003). Too often, risky situations are explained rationally by leaders and experts who are then surprised when these communications are distrusted or rejected. Research, though limited, has found that an individual’s affect-based perception of the risk significantly impacts whom and what we trust. The role of culture in how risks are perceived and experts are trusted is even less clear. Bringing together extant theory on leadership, perceived risks, trust, and culture, the present paper addresses how these forces impact trust and leadership effectiveness in an organizational setting and how effective leadership can create high impact in an organization.